HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN KEJADIAN KARIES GIGI SULUNG PADA ANAK UMUR 4 - 5 TAHUN DI DESA KUOK - Rinda Fithriyana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
The main problem of dental and oral health in children is dental caries. Both primary and permanent teeth have a risk of caries, but the decay process of primary teeth spreads more rapidly, extends and is more severe than permanent teeth. The purpose of this study was to determine the relationship between the socioeconomic status of parents and the incidence of primary dental caries in children aged 4-5 years in Kuok Village. This type of research is analytic with cross sectional design. The population in this study were all children aged 4-5 years and parents in Kuok Village with a sample of 406 people. The sampling technique used was purposive sampling technique with a sample size of 40 people. The data collection tool used was a questionnaire with univariate and bivariate data analysis using the chi square test. The results of statistical analysis obtained a significant value of p value = 0.033 (p value â‰¤ Î± 0.05). This means that there is a significant relationship between socioeconomic status and the incidence of primary dental caries in children aged 4-5 years in Kuok Village. Parents should pay more attention to their children's dental health. Parents should routinely check their children's teeth at a dentist or health service facility every 6 months.